An unusual presentation of central nervous system tuberculosis with cerebral venous sinus thrombosis in a young male - Rajagopal Srinath; Subrat Kumar Nanda; Ankit Mathur; Manish Sharma (Journal of Marine Medical Society, 2022)
Tubercular meningitis is prevalent in India as various clinical subtypes. Our case illustrates an unusual presentation of tuberculosis (TB) meningitis with cerebral venous sinus thrombosis. Our patient had presented with fever and headache for about 1 week, followed by acute onset left hemiparesis. His evaluation revealed features of cerebral venous sinus thrombosis (CVT) on neuroimaging along with cerebrospinal fluid picture of the central nervous system (CNS) TB. He was managed with antitubercular therapy with steroids and anticoagulation following which the patient recovered. The coexistence of CVT with CNS TB is very rare. It is pertinent to diagnose the same early to prevent life-threatening complications.